E-cigarette vapour enhances pneumococcal adherence to airway epithelial cells. Issue 2 (8th February 2018) - Miyashita, Lisa; Suri, Reetika; Dearing, Emma; Mudway, Ian; Dove, Rosamund E; Neill, Daniel R.; Van Zyl-Smit, Richard; Kadioglu, Aras; Grigg, Jonathan
E-cigarette vapour contains free radicals with the potential to induce oxidative stress. Since oxidative stress in airway cells increases platelet-activating factor receptor (PAFR) expression, and PAFR is co-opted by pneumococci to adhere to host cells, we hypothesised that E-cigarette vapour increases pneumococcal adhesion to airway cells. Nasal epithelial PAFR was assessed in non-vaping controls, and in adults before and after 5 min of vaping. We determined the effect of vapour on oxidative stress-induced, PAFR-dependent pneumococcal adhesion to airway epithelial cells in vitro, and on pneumococcal colonisation in the mouse nasopharynx. Elemental analysis of vapour was done by mass spectrometry, and oxidative potential of vapour assessed by antioxidant depletion in vitro . There was no difference in baseline nasal epithelial PAFR expression between vapers (n=11) and controls (n=6). Vaping increased nasal PAFR expression. Nicotine-containing and nicotine-free E-cigarette vapour increased pneumococcal adhesion to airway cells in vitro . Vapour-stimulated adhesion in vitro was attenuated by the PAFR blocker CV3988. Nicotine-containing E-cigarette vapour increased mouse nasal PAFR expression, and nasopharyngeal pneumococcal colonisation. Vapour contained redox-active metals, had considerable oxidative activity, and adhesion was attenuated by the antioxidant N-acetyl cysteine. This study suggests that E-cigarette vapour has the potential to increase susceptibility to pneumococcal infection. Exposure of airway cells to E-cigarette vapour upregulates a receptor used by pneumococci to adhere to cells http://ow.ly/p9Be30hE5B1